2010
DOI: 10.1002/sia.3156
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray photoelectron analysis of surface functional groups on diamond‐like carbon films by gas‐phase chemical derivatization method

Abstract: a Oxygen-related surface functional groups on diamond-like carbon (DLC) films were derivatized with fluorine-and nitrogenrelated groups by the gas-phase chemical derivatization (GCD) method, and the groups were analyzed quantitatively by X-ray photoelectron spectroscopy (XPS). It is desirable that a derivatization reaction is unique to the target group; however, it usually causes undesirable side reactions which affect other groups. This diversity of the reactions has complicated the analysis. In this report, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 54 publications
1
13
1
Order By: Relevance
“…17,18 These active oxygen species, especially singlet state species, have a strong oxidative power; they oxidize the alkyl-terminated groups (-R) of SAMs and polymers to polar functional groups (OH, COOH and CHO), and convert their surfaces to become more hydrophilic. 31 These labeling reagents are not chemospecific for OH, CHO and COOH. [17][18][19] VUV irradiation of methyl-terminated organosilane SAMs showed that the active oxygen species gradually decayed the carbon skeleton of SAMs, by introducing new polar groups, until complete elimination of SAMs, and these chemical conversions were reflected on the surface properties, especially wettability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 These active oxygen species, especially singlet state species, have a strong oxidative power; they oxidize the alkyl-terminated groups (-R) of SAMs and polymers to polar functional groups (OH, COOH and CHO), and convert their surfaces to become more hydrophilic. 31 These labeling reagents are not chemospecific for OH, CHO and COOH. [17][18][19] VUV irradiation of methyl-terminated organosilane SAMs showed that the active oxygen species gradually decayed the carbon skeleton of SAMs, by introducing new polar groups, until complete elimination of SAMs, and these chemical conversions were reflected on the surface properties, especially wettability.…”
Section: Introductionmentioning
confidence: 99%
“…With elongation of the VUV irradiation period, the backbone of SAMs and polymers is gradually degraded until complete dissociation. [31][32][33][34][35] Almost all previous reports have referred to chemical modifications of polymers and SAM molecules without discerning and realizing the method to achieve these modifications. These new polar groups on surface of SAMs act as anchor groups for multilayer assembly and biomolecule immobilization, [20][21][22][23] so that VUV irradiation offers a significant and accurate method for micro-nanoscale lithography, especially SAM patterning, 24 and such micro-nanopatterned SAMs will be enormously important for different technological applications.…”
Section: Introductionmentioning
confidence: 99%
“…XPS spectra were calibrated using the main C1s peak component, which is well characterised in the literature. Works in the literature specify spectra of DLC films should be calibrated to the hydrocarbon (CHx) peak at 284.4 eV (19)(20)(21)(22). Calibration shifted the spectrum by 1.2 eV, correcting for charging issues.…”
Section: X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 99%
“…F 1 s and N 1 s ) are more sensitive than the C 1 s spectra, the evaluation of oxygen‐related surface functional groups becomes obvious. In addition, the authors improved the GCD‐XPS analysis by introducing a simple mathematical treatment to exclude the influence of side reactions . However, this improved GCD‐XPS analysis still has a drawback.…”
Section: Introductionmentioning
confidence: 99%